The Legal Protection for Land Deed Officials Regarding the Making of Deeds Based on Incorrect Information by the Parties - Siswanti, Siswanti (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This research has the following objectives, namely first, to guarantee legal certainty over authentic deeds made by the Land Deed Deed Official (PPA)T against incorrect information on the parties; secondly, to provide legal protection for the Land Deed Making Officer (PPAT) who draws up an authentic deed in the form of a sale and purchase deed based on incorrect information from the parties; third, an example of waiver of rights if it turns out that there is incorrect information from the parties in accordance with Article 51 paragraph 2 of the Criminal Code. This study uses a normative juridical research approach, and the theory used in this paper is Gustav Radbruch's Legal Certainty Theory and Philip M. Hadjon's Legal Protection. The research results conclude. 1) The deed of the official making the land deed (PPAT) will not have legal certainty if the authentic deed is not in accordance with the applicable provisions or is carried out against the law. 2) Legal protection for the Land Deed Making Officer (PPAT) who draws up a deed on the basis of incorrect information from the parties is only based on the right of refusal, if he does not have bad rights then the right of refusal does not apply. A notarial deed made based on a letter or document from the parties which is known to be fake after the deed is made remains an authentic deed as long as the notary in making the deed meets the formal requirements of a deed is said to be an authentic deed. If the notary commits negligence so that he does not meet the formal requirements of an authentic deed, then the deed made by a degraded notary only has the power of proof as an underhand deed. Notarial deeds that are degraded into private deeds are regulated in Article 41, Article 44 paragraph (5), Article 48 paragraph (3), Article 49 paragraph (4), Article 50 paragraph (5), Article 51 paragraph (4). If the negligence committed by a notary results in losses for the parties, the parties can claim fees, compensation and interest from the notaryKeywords: Certainty; Deed; Protection.